Probing the wet cupping therapy (bekam) on measurable beneficial health effects - Ismail, Ab. Aziz Al Safi (Universiti Sains Malaysia, 2014)
Introduction : Cupping is a form of complementary medicine practiced in many countries worldwide. It is a method involving the application of suction to certain part of the body by placing a vacuum cup or jar. Suction for vacuum effect resulted from usage of fire or suction pump. The purposes of this therapy are curing certain diseases by extracting the blood that is believed to be harmful from the body. Objective : The aim of this study was to determine the effect of wet cupping therapy in non diabetic and diabetic subjects on body mass index (BMI), blood pressure, biochemical parameters, renal function and endothelial function. Methods : Ninety three subjects aged between 30 and 60 years old participated in this study. Sixty two non diabetic individual without chronic disease were randomly and equally assigned into control and intervention group. For diabetic group, 31 subjects were included. Cupping were done on subjects in the intervention and diabetic group, whereas individual in the control group were remained unintervene. Two sessions of wet cupping had been performed; at the start of the study and at the third month. Assessments were done at baseline, first month, third month (before the >econd session of cupping) and fourth month for all participants. Results : In non diabetic cupping group, there were significant reductions in fasting blood sugar (FBS) and all renal function parameters (serum urea, creatinine and uric acid) from baseline to the first, third and fourth month. Serum triglycerides and systolic blood pressure (SBP) also showed significant reductions at first month. All serum lipid profiles except serum triglycerides showed significant improvement at third and fourth months. The Von Willebrand Factor (VWF) antigen also showed significant reduction at fourth month. At the end of the study, all the serum lipid profiles, FBS, serum urea and creatinine in cupping group were significantly differ as compared with control group. For serum HDL-C and LDL-C, the significant difference between cupping and control group were seen at the third and fourth month. In diabetic group, FBS, blood pressure and all renal function parameters showed significant reduction at the first, third and fourth month. Serum total cholesterol showed reduction at the third and fourth month. For serum HDL-C, serum LDL-C and VWF antigen, the changes were seen at fourth month. At the end of fourth month, there were significant improvements in all parameters except BMI and triglycerides. Conclusions : Wet cupping therapy showed significant improvement in blood pressure and certain component of biochemical parameters, renal function parameters and also endothelial functions. Therefore wet cupping could contribute in reducing and preventing the risk factors for cardiovascular disease